Branch and bound algorithm for transmission system expansion planning using a transportation model - Haffner, S.; Monticelli, A.; Garcia, A.; Mantovani, J.; Romero, R. (Institute of Electrical and Electronics Engineers (IEEE), 2000)
A method for optimal transmission network expansion planning is presented. The transmission network is modelled as a transportation network. The problem is solved using hierarchical Benders decomposition in which the problem is decomposed into master and slave subproblems. The master subproblem models the investment decisions and is solved using a branch-and-bound algorithm. The slave subproblem models the network operation and is solved using a specialised linear program. Several alternative implementations of the branch-and-bound algorithm have been rested. Special characteristics of the transmission expansion problem have been taken into consideration in these implementations. The methods have been tested on various test systems available in the literature.